2003
DOI: 10.1046/j.1365-201x.2003.01108.x
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemic preconditioning alters the energy metabolism and protects the ischaemic myocardium in a stepwise fashion

Abstract: We present for the first time concordant energy metabolic and morphometric data in support of IP being a stepwise phenomenon for protection of the ischaemic myocardium. Furthermore, IP resulted in proportionally higher levels of hypoxanthine (relative to inosine) in the ischaemic myocardium, suggesting a different handling of adenine nucleotide breakdown products in the IP myocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 38 publications
(54 reference statements)
3
12
0
2
Order By: Relevance
“…This would be consistent with graded responses to Precon stimuli (107,187) and could explain variable data regarding age and Precon: studies of more profound Precon stimuli may detect efficacy in older hearts, while those using lower subthreshold stimuli may not. However, other investigations (86) identifying age-related abnormalities in cardioprotection have found that an enhanced stimulus is unable to overcome these changes.…”
Section: Age and Disease Dependence Of Cardioprotectionsupporting
confidence: 54%
“…This would be consistent with graded responses to Precon stimuli (107,187) and could explain variable data regarding age and Precon: studies of more profound Precon stimuli may detect efficacy in older hearts, while those using lower subthreshold stimuli may not. However, other investigations (86) identifying age-related abnormalities in cardioprotection have found that an enhanced stimulus is unable to overcome these changes.…”
Section: Age and Disease Dependence Of Cardioprotectionsupporting
confidence: 54%
“…Our presumption is that lower levels of interstitial lactate during coronary ligation reflect events in the myocardium local to the catheter membrane, which is managing a longer period of ischemia with lower levels of lactate production. Earlier observations 20 in pig coronary occlusion models where injury/infarct and pre‐conditioning with myocardial protection have been validated have shown similar patterns of decrease in lactate production in a ‘protected’ myocardium during a 40‐min coronary occlusion.…”
Section: Discussionsupporting
confidence: 52%
“…Myocardial IPC was created by temporary snare-occlusion for 10 min followed by reperfusion during 20 min, repeated four times [20]. Coronary venous samples (10 mL each) were collected every second minute during a 20 min period, starting 20 min after last LAD snare release.…”
Section: Methodsmentioning
confidence: 99%